Desafios e possibilidades da atuação de intérpretes educacionais para a inclusão de alunos surdos na educação básica - Silva, Luiza Trindade da (Universidade Federal de São Carlos, 2022)
The present work shares the analyzes carried out from the research of the Course Completion Work (TCC) of the Bachelor's Degree in Translation and Interpretation in Libras/Portuguese Language. The research aimed to investigate the dilemmas and possibilities of the performance of educational interpreters in the early and final years of elementary school, bringing considerations of the inclusion of deaf students in basic education and its impact on the training of translators and interpreters of Libras. The research problematized the dilemmas of this process for 3 aspects: 1) the performance of the educational interpreter, demarcating his function in the face of the articulated relations between the regent teacher and the Educational Interpreter (EI), 2) the challenges and possibilities for the performance of the EI in basic education and 3) the dilemmas and creation of strategies for interaction with deaf teachers and students at school. In order to answer these questions, a bibliographical survey of research was carried out that underlies the current dilemmas of deaf education and the presence of translators and interpreters as mediation agents between teachers, deaf students and the school context. For data collection, interviews were conducted with 2 professional educational interpreters who work or have worked in interpretive mediation for the deaf in basic education, focusing on basic education. It is expected that such knowledge can directly help in the formation of EI and in its interpretative and educational practices with deaf students in the context of school inclusion.
Challenges and possibilities of the performance of educational interpreters for the inclusion of deaf students in basic education
Keywords: Educação de surdos; Interpretação Libras/Língua Portuguesa; Formação de tradutores e intérpretes de Libras; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO